Smart City Pilot Policy and Urban Productivity in China: Based on Difference-in-Differences Model - Yao, Jiahui (Transactions on Economics, Business and Management Research, 2024)
Urban productivity is a key indicator to measure urban economic performance, which is related to the competitiveness of cities and the economic development of countries and regions. To clarify the mechanism of constructing smart cities and urban productivity, using the panel data of 284 prefecture-level cities from 2011 to 2020, this paper constructs a difference-in-differences model for empirical tests. The study found that the construction of smart cities can promote urban productivity. Meanwhile, the mechanism tests indicate that smart cities mainly improve urban productivity through technological innovation, advanced industrial structure and digital financial empowerment. According to heterogeneity analysis, smart cities in eastern cities and large cities significantly promote urban productivity, while the promotion effect of smart cities in central and western cities and small cities was not significant. This study has vital reference significance for guiding the construction of smart cities and exploring how to improve urban productivity.